Operational principles of three-phase single active bridge DC/DC converters under duty cycle control - Sang,Y; Junyent,Ferre A; Green,TC (IEEE Transactions on Power Electronics, 2020)
Single Active Bridge (SAB) DC/DC converters are attractive options for unidirectional DC/DC conversion in future medium power generation applications, offering galvanic isolation and a diode-based output side. SAB DC/DC converters must be controlled by adjusting the active bridge switching duty cycle, unlike Dual Active Bridge (DAB) converters where the phase-shift angle control is normally used. This paper presents a comprehensive analysis of the operational principles of three-phase SAB (3p-SAB) DC/DC converters that arise from different duty cycle operation ranges. Moreover, the converter performances such as transformer harmonic currents are analyzed and are compared between different input and output DC voltage conditions. Finally, an experimental validation using a small scale prototype is presented.